Exercise: The key to enhancing sleep quality and physical function in Parkinson’s disease? A systematic review and meta-analysis - Zhiqin Li; Pingqing Hu (PLoS ONE, 2025)
Parkinson’s disease (PD) is a significant neurodegenerative disorder that affects millions of individuals worldwide and currently has limited effective treatment options. Exercise has been proposed as a non-pharmacological intervention to improve both motor and non-motor symptoms in PD. This study aims to systematically review and meta-analyze the impact of exercise interventions on sleep quality and physical functioning in PD patients. A comprehensive search of the literature up to December 15, 2023, identified randomized controlled trials that evaluated exercise interventions in PD patients. The primary outcomes were sleep quality, motor function, balance, gait performance, and quality of life. A total of 62 studies with 3,274 participants were included in the analysis. Exercise interventions led to significant improvements in sleep quality [SMD = −0.55, 95% CI (−0.91, −0.18), p = 0.003], motor capability [SMD = −0.47, 95% CI (−0.66, −0.28), p < 0.01], balance ability [SMD = 0.53, 95% CI (0.33, 0.74), p < 0.0001], gait performance [TUGT: SMD = −0.44, 95% CI (−0.60, −0.29), p = 0.0017; stride velocity: SMD = 0.38, 95% CI (0.15, 0.60), p = 0.001; step length: SMD = 0.32, 95% CI (0.10, 0.54), p = 0.004], and quality of life [SMD = −0.38, 95% CI (−0.73, −0.03), p = 0.04] ( p < 0.05). Exercise is an effective intervention for enhancing sleep quality and improving physical function in PD patients. These findings underscore the importance of incorporating exercise into the management strategies for PD.